The Affirmation Special Allocation Fund and Regional Economic in Indonesia - Soraya, Amanda Petty; Qibthiyyah, Riatu Mariatul (Universitas Negeri Semarang, 2020)
Starting 2015, Government of Indonesia introduced Affirmation Special Allocation Fund (DAK). Affirmation DAK is expected to fund infrastructure, accessibility and improvement of basic services, as well as aiming to accelerate development in disadvantaged areas, border areas, outer islands, and transmigration areas. These targeted regions on average have low GRDP per capita. The purpose of this study is to determine the effect of Affirmation DAK on the regional economy in Indonesia. The existence of Affirmation DAK is expected to support equal distribution of basic infrastructure and services and accelerate development in Affirmation DAK receiving area which is a region with characteristics of disadvantaged areas, border areas, outermost islands and transmigration areas. This study uses panel data of 491 regencies/municipalities in 2011-2018Ã‚Â and using the fixed effect estimation method. Empirical results show that Affirmation DAK has not had a positive effect on GRDP per capita. Limiting estimation only to Affirmation DAK recipient regions, there is also no positive association between Affirmation DAK and GRDP per capita. The results of this study also show that the impact of Affirmation DAK is very small on the recipient area, implying that Affirmation DAK in its current form and existing pool fund size, has not yet an effective policy for regions exiting from Ã¢â‚¬Å“the lagging regions trapÃ¢â‚¬Â. It is instead, still, revenue sharing and general allocation fund (DAU), that have consistent positive effect on regional economic growth, both are block grants that to an extent related to more discretionary to local governments in terms of use of fund.